ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK BUMI DAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH DI KOTA DENPASAR TAHUN 2009-2013 - Damaiyanti, Dian; Setiawan, Ery (E-Jurnal Akuntansi; Vol 9 No 1 (2014), 2014)
Taxation sector contributes significantly to the revenue of a State government. Tax revenue is revenue that can be relied upon as financing development, especially the development of local government. Land and Building Tax continues to increase along with the increase of economic growth as well as ownership of the land and/or buildings, especially in the city of Denpasar. The purpose of this study was to examine the effectiveness and contribution of land and building tax receipt to the original income Denpasar in 2009-2013. By using quantitative analysis techniques, the results showed that the effectiveness of land and building tax receipts in 2009-2013 is very effective with an average of over 100 per cent, which is 121.42 percent. Contribution of land and building tax receipt to the original income shows less results with an average below 50 percent, which is 18.62 percent.
Keywords: effectiveness, contributions, property tax